The Identifikasi Delineasi Oli Berdasarkan Nilai Resistivitas Menggunakan Metode Geolistrik Di Area “X” Tana Tidung, Kalimantan Utara - Wibowo, Nobella Hadi; Djayus, Djayus; Supriyanto, Supriyanto (GEOSAINS KUTAI BASIN, 2023)
Waste pollution is a problem that must be addressed immediately. Apart from affecting the air and waters, sewage pollution can also seep below the ground surface. One of the causes of waste pollution in area "X" is the leakage of the oil storage tank by the PLTD (Diesel Power Plant) operational system in that area. This leak causes oil droplets to be absorbed into the pores of the soil and into the subsurface where it settles. To find out whether remnants of oil seepage remained in area "X" a study was conducted using the resistivity geoelectric method. The research was carried out in 2 ways, namely processing in 2 and 3 dimensions and using coring samples as a comparison of resistivity values. There were 6 coring sampling points (interval variation of 7 parts of depth) used in the study, namely coring A, B, C, D, E and F. From the six samples, an average resistivity value of 2.637 Ωm is obtained at a depth of 0-30 cm . Furthermore, at a depth of 100-130 cm it has an average resistivity value of 2.702 Ωm, at a depth of 200-230 cm it has an average resistivity value of 3.510 Ωm, at a depth of 300-330 cm it has an average resistivity value of 1.862, at a depth of 400- 430 cm has an average resistivity value of 1.928 Ωm, at a depth of 500-530 cm has an average resistivity value of 1.610 Ωm and at a depth of 600-630 cm has an average resistivity value of 1.637 Ωm. The results of this study indicate that soil contaminated with waste oil has a lower resistivity, which is in the range of 2.30 Ωm to 3.76 Ωm.